Occupational health problems of municipal solid waste management workers in India - Navtej kaur (South Eastern European Journal of Public Health, 2025)
Purpose: Occupational health risks are potential negative health effects that one may experience while working. Around the globe, 2.1 billion tonnes of garbage are created annually, and municipal solid waste workers (MSW) or municipal workers often handle this rubbish. They put in a lot of overtime, so managing the garbage generated is not a simple chore. Throughout the waste management process, Municipal Solid Waste (MSW) employees encounter occupational pressures that negatively impact their well-being and lead to a high prevalence of occupational health issues. To protect MSW workers' safety and wellbeing, it is essential to comprehend their work practices and occupational morbidities. Aim: The objective of this research was to evaluate the occupational health issues that municipal solid waste management employees face. Method: In this regard, the research sought to investigate the workplace safety and occupational health practices of MSW employees in Karnataka, India. A cross-sectional descriptive research was carried out among Karnataka, India's solid waste management employees. The research comprised all 408 employees, of whom 313 (77%) took part. Direct interviews and clinical examinations utilising a standardised questionnaire were used to gather data. Clinical examination revealed the observed morbidity, which included nail infections, dermatological issues, ocular disorders, and respiratory ailments. Self-reported complaints and physician diagnoses were used to determine the point prevalence of additional occupationally associated health events that occurred during the study period or during the one-month recall period and that happened after entering the current occupation. Results: 42.5 ± 7.2 years was the average age. The observed morbidity, which varied from 21% to 47%, was substantial and included respiratory, ocular, dermatological, and nail infections. Occupational morbidities such as falls (63.6%), accidents (22%), injuries (73.2%), and aquatic vector-borne diseases (7.1%) were observed to be quite prevalent. All of the main joints are affected by the present prevalence of musculoskeletal morbidities (17–39%). Conclusion: The miserable conditions of employment and high workplace morbidities among MSW workers in Karnataka, India, are highlighted in this research. The MSW personnel found it challenging since the workplace lacked basic facilities. Socioeconomic status, education, and unfavourable working circumstances all contribute to the likelihood of occupational risks. The many health effects that municipal employees experience while working are highlighted in this article. It is necessary to establish a holistic strategy that prioritises the MSW workers' health and safety while including social security. Waste handlers must have access to ergonomically designed protection gear, clean drinking water, and facilities for washing and sanitation throughout working hours in order to enhance their working conditions.